1994
DOI: 10.1002/aic.690400403
|View full text |Cite
|
Sign up to set email alerts
|

Modeling, simulation and kinetic parameter estimation in batch crystallization processes

Abstract: IntroductionThe onset of instability in industrial continuous crystallization processes in response to small disturbances has previously been shown to be determined primarily by the strong nonlinear dependence of nucleation rates on the relative supersaturation driving force (Buyevich et al., 1991;Jager et al., 1991). Consequently, accurate kinetic modeling of crystallization kinetics, especially nucleation, is a prerequisite to the optimal design and control of crystallization processes. Seeded batch experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Secondary nucleation rates in power law models are generally assumed to be the result of the energy transfer to the crystal, the efficiency of contact, and the survival of the fine particles formed. Anisi and Kramer discussed the general simple power law model and described the secondary nucleation with a power law function from the aspects of saturation, crystal mass fraction, and turbulence in the mold, as shown in eq where, ε is the dissipated power, φ T the volumetric holdup, σ the degree of supersaturation, and K SN , n 1 , and a are the fitting parameters.…”
Section: Secondary Nucleation Modelmentioning
confidence: 99%
“…Secondary nucleation rates in power law models are generally assumed to be the result of the energy transfer to the crystal, the efficiency of contact, and the survival of the fine particles formed. Anisi and Kramer discussed the general simple power law model and described the secondary nucleation with a power law function from the aspects of saturation, crystal mass fraction, and turbulence in the mold, as shown in eq where, ε is the dissipated power, φ T the volumetric holdup, σ the degree of supersaturation, and K SN , n 1 , and a are the fitting parameters.…”
Section: Secondary Nucleation Modelmentioning
confidence: 99%
“…The overall effects of death and birth of crystals may be accounted as experimental deviations from an ideal batch operation The initial and boundary conditions for solving Eq. 1, as described by Farrell and Tsai (1994), are The nucleation rate and the independent‐size growth rate equations, expressed as power‐law functions, include a power‐law term to account for the effect of agitation, as recommended by Qiu and Rasmunson (1994): The total mass of crystals formed is calculated as a function of the third moment in which the third moment is calculated as The overall mass balance and its initial condition become …”
Section: Mathematical Modelmentioning
confidence: 99%
“…19 and 20, it is important to note the range of applicability of these predictions. For crystallization, Farrell and Tsai (1994) discussed the importance and difficulty of accurately determining kinetic parameters for various process conditions. Hill and Ng (1996b) showed that empirical data for multiple particle breakage can be represented by various breakage function parameters.…”
Section: Model Parameters With Particle-size Distributionmentioning
confidence: 99%